Pembelajaran Jarak Jauh Masa Pandemi Covid-19 - Suparman, Atwi; Andriani, Susi; Trihardini, Ayu (Fenghuang: Jurnal Pendidikan Bahasa Mandarin, 2022)
The Covid-19 pandemic has made the education world adapt rapidly. During this pandemic era, the face-to-face learning is avoided and distance learning (PJJ) is adaptively applied at various levels of education, neither formal nor non-formal. In its implementation, distance learning is institutional-based learning activity and is a part of formal education, so it has different forms and tools differ from so called self-taught learning. More over, educational interactions between teachers and students are carried out at a distance apart. Necessarily, distance learning should be implemented with careful planning and preparation. Considering the fact that most of the distance learning activities during the COVID-19 pandemic were carried out suddenly and without prior planning, this paper is expected to provide input to the organizers of this sudden distance learning. This paper provides a description of PJJ, including types of PJJ, PJJ teaching materials, and PJJ constellations.